The effects of dietary intervention with turmeric on lipid profile and anthropometric indices in overweight/obese women with hyperlipidemia: a randomized controlled clinical trial - Atakan, Ayşegül; Kabaran, Seray; Eren, Fatma Hülyam (Progress in Nutrition, 2022)
Background and Objective: The objective of this trial was to evaluate the effects of turmeric on blood lipids and body weight loss in overweight/obese women with hyperlipidemia.Methods and Study Desing: In this randomized controlled trial, overweight/obese hyperlipidemic women (BMI>25 kg/m2) were randomly divided into 2 groups as turmeric (n=35; 4 g/d) and control (n=35) groups for 8 weeks. The subjects included in the turmeric and control groups adhered to a medical nutrition therapy. Serum lipid profile and anthropometric data were measured at the beginning and again at the end of the study.Results: After 8 weeks of dietary intervention, both turmeric and control groups showed significant decreased in total cholesterol (‑55.66 versus ‑53.06 mg/dl), LDL‑C (‑35.70 versus ‑35.91 mg/dl) and TG (‑44.34 versus ‑42.03 mg/dl), respectively (p